2005
DOI: 10.1007/s00122-004-1877-4
|View full text |Cite
|
Sign up to set email alerts
|

Barley Dhn13 encodes a KS-type dehydrin with constitutive and stress responsive expression

Abstract: Dehydrins (DHNs) compose a family of intrinsically unstructured proteins that have high water solubility and accumulate during late seed development, low temperature or water deficit conditions, and are thought to play a protective role in freezing and drought tolerance in plants. Twelve Dhn genes were previously described in the barley genome. Here, we report an additional member of this multigene family, Dhn13. The Dhn13 gene is located in chromosome 4 near marker MWG634 and encodes a 107-amino acid KS-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 34 publications
1
42
0
2
Order By: Relevance
“…Microarray data showed a considerable increase of Dhn13 transcripts when plants were subjected to chilling and freezing temperatures. Rodriguez et al (2005), supporting our results, also found that there were somewhat elevated transcript accumulation of the Dhn13 gene in barley under drought stress. Compared with Dhn6 and Dhn11, lower accumulation of Dhn13 during dehydration may be due to less efficient signaling pathways and transcriptional activators.…”
Section: Differential Expression Of Dhn Genessupporting
confidence: 91%
See 1 more Smart Citation
“…Microarray data showed a considerable increase of Dhn13 transcripts when plants were subjected to chilling and freezing temperatures. Rodriguez et al (2005), supporting our results, also found that there were somewhat elevated transcript accumulation of the Dhn13 gene in barley under drought stress. Compared with Dhn6 and Dhn11, lower accumulation of Dhn13 during dehydration may be due to less efficient signaling pathways and transcriptional activators.…”
Section: Differential Expression Of Dhn Genessupporting
confidence: 91%
“…The Dhn gene family encodes for several proteins that are typically accumulated during the maturation-drying phase of seed development, in seedlings, or more mature plants in response to environmental stresses (Shinozaki and YamaguchiShinozaki 1997;Zhu et al 2000). In the barley genome, recent investigations into the dehydrin multigene family have identified 13 Dhn genes, which encode four subclasses of DHNs, Y n SK n , SK n , K n and KS, based on permutations in the arrangement of characterized domains [reviewed in Campbell and Close (1997), Werner-Fraczek and Close (1998), Choi et al (1999Choi et al ( , 2000, Svensson et al (2002), Rodriguez et al (2005)]. Transcriptome analyses based on microarrays have provided powerful tools for the discovery of stressresponsive genes, not only in Arabidopsis, but also in various crop plants and tree species (Shinozaki and Yamaguchi-Shinozaki 2007).…”
mentioning
confidence: 99%
“…Changes in membrane composition , organic acids (Timpa et al, 1986), accumulation of osmolytes (Hitz et al, 1982;Timpa et al, 1986), and synthesis of stress protection proteins (hsps, Late Embryogenesis Abundant proteins, etc. ; Burke et al, 1985b;Rodriguez et al, 2005) all contribute to the rate of tissue decline in the high respiratory environment used in the bioassay. Further study is needed to determine the overall contribution of individual metabolic pathways to the observed water-deficit stress responses of this bioassay.…”
Section: Impact Of Sampling Time On the Stress Test Determinationmentioning
confidence: 99%
“…Some DHNs are expressed constitutively during normal growth (Nylander et al, 2001;Rorat et al, 2004Rorat et al, , 2006Rodriguez et al, 2005). DHNs exist in a wide range of photosynthetic organisms, including angiosperms, gymnosperms, algae, and mosses (Svensson et al, 2002).…”
mentioning
confidence: 99%